The Partnership Model for Women Farmers by Processing Mangosteen Skin Waste as a Functional Food Substitute - Humaira, Linar; Jannah , Asmanur; Fitriani , Anna; Maad, Faizal (CV. Inara, 2021)
Mangosteen fruit is a leading commodity from Barengkok Village, Leuwiliang sub-district, Bogor, as well as a commodity capable of penetrating exports. The environmental problem that arises during the harvest season and from fruit that does not pass export is the waste of its skin, so it is necessary to make use of it so that it has economic value for the community. This study examines a community partnership model through community empowerment in the use of mangosteen peel waste as a substitute for functional food. This study is based on the Women Farmers Group with a descriptive qualitative approach, demonstrations and training on the development of functional food processed products and assistance. The results of the study show that people's understanding and insights have increased from 50% who don't know to 100% of participants who know and understand how to use mangosteen peel into food processing, partners are able to independently produce processed products based on mangosteen peel flour with a turnover of 16 jars per month. Technological innovation in processing mangosteen peel into food, motivates people to become new entrepreneurs, because the product is unique and healthy and has a selling value. This partnership program provides solutions to address the environment and create additional income for the community.